The Quebec Act Respecting Reserved Designations and Added-Value Claims: Innovative Regulations in North America for Terroir and Specificity Products - Niogret, Baudouin (Cuizine, 2010)
The Conseil des appellations réservées et des termes valorisants (CARTV) is the governing body responsible for the management and protection of reserved designations in Quebec. This article explores the challenges faced by CARTV in the implementation of the Act Respecting Reserved Designations and Added Value Claims, an innovative regulation in North America. One major challenge is that the voluntary nature of the regulation makes it more difficult to enforce. Disseminating information about the regulations to the local industry actors most affected by them is crucial, as they effectively allow for its success or failure; it is also important to convince all participants to act in a spirit of collective interest. Further, it is necessary to adapt the principles of reserved designations to the specific conditions of the landscape. To follow the examples of regions where such regulations have been most successfully applied, going forward it would be highly beneficial for Quebec to use reserved designations as a means of favouring rural development and acknowledging the multifaceted function of agriculture.